Decreased production of TNF-alpha by lymph node cells indicates experimental autoimmune encephalomyelitis remission in Lewis rats - Seger, Juliana; Zorzella-Pezavento, Sofia Fernanda Gonçalves; Pelizon, Ana Cláudia; Martins, Douglas Rodrigues; Domingues, Alexandre [UNESP]; Sartori, Alexandrina [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2010)
Experimental autoimmune encephalomyelitis (EAE) is mediated by CD4+ Th1 cells that mainly secrete IFN-γ and TNF-α, important cytokines in the pathophysiology of the disease. Spontaneous remission is, in part, attributed to the down regulation of IFN-γ and TNF-α by TGF-β. In the current paper, we compared weight, histopathology and immunological parameters during the acute and recovery phases of EAE to establish the best biomarker for clinical remission. Female Lewis rats were immunised with myelin basic protein (MBP) emulsified with complete Freund's adjuvant. Animals were evaluated daily for clinical score and weight prior to euthanisation. All immunised animals developed the expected characteristics of EAE during the acute phase, including significant weight loss and high clinical scores. Disease remission was associated with a significant reduction in clinical scores, although immunised rats did not regain their initial weight values. Brain inflammatory infiltrates were higher during the acute phase. During the remission phase, anti-myelin antibody levels increased, whereas TNF-α and IFN-γ production by lymph node cells cultured with MBP or concanavalin A, respectively, decreased. The most significant difference observed between the acute and recovery phases was in the induction of TNF-α levels in MBP-stimulated cultures. Therefore, the in vitro production of this cytokine could be used as a biomarker for EAE remission.
Keywords: experimental autoimmune encephalomyelitis; tumor necrosis factor; alpha; rats inbred Lew; biomarkers